2019
DOI: 10.3390/molecules24030546
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Potential Biological Activities of Essential Oil from Rice Leaf

Abstract: Although many investigations on phytochemicals in rice plant parts and root exudates have been conducted, information on the chemical profile of essential oil (EO) and potent biological activities has been limited. In this study, chemical compositions of rice leaf EO and in vitro biological activities were investigated. From 1.5 kg of fresh rice leaves, an amount of 20 mg EO was obtained by distillation and analyzed by gas chromatography-mass spectrometry (GC-MS), electrospray ionization (ESI), and atmospheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
(49 reference statements)
2
9
0
Order By: Relevance
“…Studies have shown that essential oils include a large content of antioxidants donating hydrogen in oxidative reactions, especially in the presence of light. Essential oils were also recognized to exhibit antifungal and antibacterial properties hence preventing plants from possible pathogenic triggers [26][27][28]. Upon biotic/abiotic stress conditions, essential oils can release their chemical substituents through a range of molecular interactions [29] and each of them exhibits different mechanisms of actions on microorganism [30].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that essential oils include a large content of antioxidants donating hydrogen in oxidative reactions, especially in the presence of light. Essential oils were also recognized to exhibit antifungal and antibacterial properties hence preventing plants from possible pathogenic triggers [26][27][28]. Upon biotic/abiotic stress conditions, essential oils can release their chemical substituents through a range of molecular interactions [29] and each of them exhibits different mechanisms of actions on microorganism [30].…”
Section: Discussionmentioning
confidence: 99%
“…The β-carotene bleaching test antioxidant activity (lipid peroxidation) of the aqueous and 70% ethanolic extracts was done by the method of Minh et al . with modifications 42 . In brief, β-carotene (2 mg) (HiMedia, India) was dissolved in 10 ml of chloroform (Merck, India) and then 1 ml of the chloroform solution was added to 20 μl of linoleic acid (HiMedia-GRM10250, India) and 200 mg of Tween-80 (HiMedia-PCT1513, India).…”
Section: Methodsmentioning
confidence: 99%
“…A t and A tt are the absorbance measured after the incubation of 180 min for sample and control, respectively. Higher LPI value indicates the higher antioxidant activity 42 , 43 .…”
Section: Methodsmentioning
confidence: 99%
“…ESI-MS analysis was conducted on negative/positive ion mode [42]. APCI-MS analysis was implemented using a mass spectrometer with an electrospray ion source [43].…”
Section: Methodsmentioning
confidence: 99%